1976
DOI: 10.1111/j.1476-5381.1976.tb07671.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Peristalsis in Guinea‐pig Isolated Ileum and Colon by Drugs That Block Prostaglandin Synthesis

Abstract: 3 Aspirin (20-100 Rtg/ml) or indomethacin (1-4 ±g/ml) applied serosally greatly inhibited all aspects of peristalsis in guinea-pig ileum and colon. Inhibition of peristalsis of the ileum by aspirin was antagonized by prostaglandin E2 and that by indomethacin was removed by prostaglandin F2a or ACh. Inhibition of colonic peristalsis by aspirin was antagonized by prostaglandin E2 but rarely by ACh, and that by indomethacin by prostaglandin El or E2. Mucosal application of aspirin had little effect on either ileu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

1977
1977
2017
2017

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 21 publications
1
20
0
Order By: Relevance
“…In addition, it has been suggested that there is an inhibitory effect of [6]-gingerol or [6]-shogaol on COX in vivo and in vitro, 25,26) and that PGs contribute to peristaltic activity via a direct action on the muscle cells and stimulating nerves. 27) Since it was confirmed that PGs were involved in the present models, the inhibition of COX may contribute to the inhibitory effects of dried ginger root on accelerated small intestinal motility.…”
Section: Effect On Isolated Guinea Pig Ileummentioning
confidence: 99%
“…In addition, it has been suggested that there is an inhibitory effect of [6]-gingerol or [6]-shogaol on COX in vivo and in vitro, 25,26) and that PGs contribute to peristaltic activity via a direct action on the muscle cells and stimulating nerves. 27) Since it was confirmed that PGs were involved in the present models, the inhibition of COX may contribute to the inhibitory effects of dried ginger root on accelerated small intestinal motility.…”
Section: Effect On Isolated Guinea Pig Ileummentioning
confidence: 99%
“…However, the circular and longitudinal muscle layers interact, and it is not possible to extrapolate from muscle strips to intestinal behaviour. Despite inhibition of circular muscle strips of guinea-pig colon by prostaglandin El or E2, peristaltic activity in colonic segments was increased by these compounds (Eley, Bennett & Stockley, 1977), and decreased by aspirin (Bennett, Eley & Stockley, 1976).…”
Section: Longitudinal Musclementioning
confidence: 99%
“…It is likely that the circular muscle is relatively less excitable (or more inhibited) and requires considerable excitatory motor input to reach the threshold for contraction, whereas the longitudinal muscle layer is normally very close to threshold, judged by the presence of spontaneous contractions. This difference in state could be due to a preferential inhibition of circular muscle, but not longitudinal muscle, by prostaglandins released from damaged tissue (Bennett et al 1976;Maggi et al 1994). Another possibility is that the circular muscle, but not the longitudinal muscle, is actively inhibited by enteric inhibitory motor neurones.…”
Section: The Longitudinal Muscle In the Preparatory Phase Of Peristalsismentioning
confidence: 99%